Effect of built environment on BMI of older adults in regions of different socio-economic statuses - Zang, Peng; Chen, Kaihan; Zhang, Haifan; Qiu, Hualong; Yu, Yun; Huang, Jianwen (Frontiers in Public Health, 2023)
Background Numerous studies have ignored the influence of underdeveloped urban surroundings on the physical health of China’s ageing population. Lanzhou is a typical representative of a less developed city in China. Methods This study investigated the relationship between body mass index (BMI) and built environment amongst older adults in regions of different socio-economic statuses (SES) using data from medical examinations of older adults in Lanzhou, as well as calculating community built environment indicators for regions of different SES based on multiple linear regression models. Results Results showed that age and underlying disease were negatively associated with overall older adult BMI in the study buffer zone. Land use mix, number of parks and streetscape greenery were positively associated with older adult BMI. Street design and distance to bus stops were negatively connected in low SES regions, but population density and street design were negatively correlated in high SES areas. Conclusion These findings indicate that the built environment of SES regions has varying impacts on the BMI of older persons and that planners may establish strategies to lower the incidence of obesity amongst older adults in different SES locations.